Pengaruh Perhatian Orangtua dan Motivasi.Belajar terhadap Prestasi Belajar Siswa Kelas IV SN Negeri 1 Klepu - Adzimatnur Muslihasari; Yulia Eka Yanti; Tety Nur Cholifah (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
The decline in student achievement in schools is due to the lack of parental attention and learning motivation from students. The research objective was to determine whether there was an effect of parental attention and learning motivation on student achievement. This research was conducted at SD Negeri 01 Klepu, Sumbermanjing Wetan District. The method used in this research is descriptive quantitative method with a population of all students of SD Negeri 01 Klepu. The sampling technique was using proportionate stratified random sampling technique. Parental attention and motivation data were obtained from a questionnaire. Student achievement data obtained from documentation. The trial was conducted on 20 students of SD Negeri 01 Klepu outside the sample. The data analysis technique used multiple regression analysis. Based on the results of data analysis, conclusions can be drawn, (1) There is a significant effect of parental attention on student achievement at SD Negeri 01 Klepu. (2) There is a significant effect of learning motivation on student achievement at SD Negeri 01 Klepu. (3) There is an effect of parental attention and learning motivation on student achievement at SD Negeri 01 Klepu.